'A land of horror and vast wilderness': landscapes of crusade and Jerusalem pilgrimage in Arnold of Lübeck's Chronica Slavorum. Issue 3 (27th May 2021) - Spacey, Beth C.
ABSTRACT: Abbot Arnold of Lübeck's Chronica Slavorum (written before 1210) contains the most detailed near-contemporary account of Duke Henry the Lion's Jerusalem pilgrimage of 1172. It also includes narratives of several crusades of the twelfth and early thirteenth centuries, including Frederick Barbarossa's Holy Land campaign (1189–90) and the so-called German Crusade (1197–8). At points in his Chronica, moreover, Arnold explores the penitential opportunities posed by pilgrimage and crusade through discussion of responses to wilderness landscapes. By cueing critical reflection across different expeditions, Arnold prompts his audience to situate Henry the Lion's pilgrimage in the sacred historical continuum to which many contemporaries believed the crusades belonged. This article contends that landscapes offered Arnold a multifaceted narrative tool which he also used to evoke Old Testament models and convey what he believed had led past armed pilgrimages to fail in achieving their stated goals.